Bison wallowing alters pollinator nesting and foraging resources in shortgrass sagebrush steppe in the Northern Great Plains - Campbell, Joshua W.; Pei, C. K.; Morphew, Alex R.; Brabant, Craig M.; Spevak, Edward M. (Frontiers in Ecology and Evolution, 2025)
Bison were historically a dominant large grazer in the Great Plains but were extirpated from much of their historic range. From reintroduction efforts, we understand bison and their associated activities have keystone effects on plants and wildlife in bison-grazed areas. Their specific activities modify the soil and plant community, but these effects on invertebrate communities are less explored, despite the diverse functional roles of grassland invertebrates. Wallowing, a unique behavior of bison in which they repeatedly roll on the ground and create bare depressions, may influence nesting resources of important ground-nesting pollinators (bees and wasps). This behavior provides one of the sources of bison-associated landscape heterogeneity, but how wallowing affects ground-nesting pollinators and other insects is not well-understood. Our broad objectives were to identify ground-nesting insects using wallows as nesting sites in north-central Montana and collate a list of other bison wallow-associated arthropods documented in the literature to understand the ecological interactions associated with bison-specific disturbances to the landscape. For our field study, we used emergence traps and sweep netting surveys to compare wallow and non-wallow prairie sites to determine differences of ground-nesting bee and wasp richness and abundance. Additionally, we surveyed surrounding vegetation communities and soil compaction at wallow and non-wallow sites. Our collections of 52 taxa were dominated by various wasp families (Mutillidae, Chrysididae, Crabronidae, Pompilidae), with few bees. Overall, we found higher abundance and taxonomic richness of ground-nesting pollinators emerging from within our adjacent prairie sites compared to within wallows. Vegetation surveys revealed distinct plant communities around bison wallows compared to adjacent prairie sites, with the most common forbs being non-native species. We found a small number of studies that collectively sampled 40 arthropod families associated with wallows, but our field study is the first published data on ground-nesting pollinator use of wallows. These data increase our knowledge of bison-engineered ecological interactions and how bison reintroductions might influence ground-nesting insects such as bees and wasps within the shortgrass prairie/sagebrush steppe ecosystem of the Northern Great Plains.